2016
DOI: 10.3390/atmos7100129
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Predicting Ground PM2.5 Concentration Using Satellite Aerosol Optical Depth

Abstract: This study reviewed the prediction of fine particulate matter (PM 2.5 ) from satellite aerosol optical depth (AOD) and summarized the advantages and limitations of these predicting models. A total of 116 articles were included from 1436 records retrieved. The number of such studies has been increasing since 2003. Among these studies, four predicting models were widely used: Multiple Linear Regression (MLR) (25 articles), Mixed-Effect Model (MEM) (23 articles), Chemical Transport Model (CTM) (16 articles) and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 151 publications
2
83
0
2
Order By: Relevance
“…Once AOD unitless measurements have been calibrated with actual PM 2.5 readings from on-the-ground ambient air monitors, it is then possible to utilize the derived AOD-PM 2.5 concentration readings to estimate actual ambient PM 2.5 concentration in areas where there are no on-the-ground air monitors. The relationship between AOD measurements and on-the-ground measurements of PM 2.5 concentration readings has been confirmed in available publications [16,[27][28][29][39][40][41][42][43][44].By incorporating AOD-PM 2.5 concentration values into the currently utilized PMB, we hypothesized there would be a further improvement in the fused AOD-PM 2.5 -PMB surface [16]. Our intention, in this preliminary work, was to test this hypothesis by using these four experimental AOD-PM 2.5 and PMB fused concentration surfaces with linked health outcome data from Baltimore, Maryland, and New York City, New York, in a case-crossover epidemiologic study design data files analyzed by using conditional logistic regression [16].…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Once AOD unitless measurements have been calibrated with actual PM 2.5 readings from on-the-ground ambient air monitors, it is then possible to utilize the derived AOD-PM 2.5 concentration readings to estimate actual ambient PM 2.5 concentration in areas where there are no on-the-ground air monitors. The relationship between AOD measurements and on-the-ground measurements of PM 2.5 concentration readings has been confirmed in available publications [16,[27][28][29][39][40][41][42][43][44].By incorporating AOD-PM 2.5 concentration values into the currently utilized PMB, we hypothesized there would be a further improvement in the fused AOD-PM 2.5 -PMB surface [16]. Our intention, in this preliminary work, was to test this hypothesis by using these four experimental AOD-PM 2.5 and PMB fused concentration surfaces with linked health outcome data from Baltimore, Maryland, and New York City, New York, in a case-crossover epidemiologic study design data files analyzed by using conditional logistic regression [16].…”
supporting
confidence: 55%
“…CDC subsequently incorporated PMB into its Environmental Public Health Tracking (EPHT) network of state and New York City partners [16,18,22,26]. To date, PMB has been used by federal and state epidemiologists completing EPHT projects in different parts of the US [16,18,22,26].Within this decade, the availability and use of satellite AOD data have become more routine [6,16,[27][28][29][30][31]. Newer generation satellite instruments measure AOD with increased temporal accuracy and finer spatial resolution [27,[32][33][34][35][36][37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another proxy measurement of particle air pollution data is the AOD obtained from satellites. Previous studies on predicting PM 2.5 concentration from AOD were reviewed by Chu et al (2016). In addition, those regression-based models showed that PM 2.5 concentrations have positive relationships with AOD (Chang, Hu, & Liu, 2013;Grantham, Reich, Liu, & Chang, 2018;Kloog, Koutrakis, Coull, Lee, & Schwartz, 2011;Kloog, Nordio, Coull, & Schwartz, 2012;Lee, Liu, Coull, Schwartz, & Koutrakis, 2011;Liu, Sarnat, Kilaru, Jacob, & Koutrakis, 2005;Ma et al, 2016;Paciorek, Liu, Moreno-Macias, & Kondragunta, 2008;Yu, Liu, Ma, & Bi, 2017) because AOD measures light extinction due to particles (e.g., dust, smoke, and pollution) in the atmospheric column.…”
Section: Data Descriptionmentioning
confidence: 99%
“…For example, Liu, Sarnat, Kilaru, Jacob, and Koutrakis (2005) and Lee, Liu, Coull, Schwartz, and Koutrakis (2011) incorporated aerosol optical depth data from satellites in a linear regression model and a linear mixed model, respectively, to obtain daily ground-level PM 2.5 concentrations. A comprehensive review on estimating ground-level PM 2.5 concentrations based on aerosol optical depth can be found in the work of Chu et al (2016). Many spatial and spatio-temporal kriging models have also been developed for mapping PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%